2009
DOI: 10.1243/09544100jaero529
|View full text |Cite
|
Sign up to set email alerts
|

Aerodynamic performance of a bypass engine with fan nozzle exit area change by warped chevrons

Abstract: Abstract:Variation of the bypass nozzle exit area enables optimization of the turbofan engine operating cycle over a wider range of operational conditions resulting in improved thrust and/or fuel consumption. Two mechanisms for varying the nozzle area have been investigated. The first uses an array of chevrons which when closed, form a full body of revolution and when warped/curved, increase the exit area while forming a serrated trailing edge. The second technique incorporates an axially translating section o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Subsequently, there have been numerous investigations within the literature on the use of RANS CFD for the calculation of aerodynamic performance metrics for civil separate-jet nozzles [13,14,15,16]. Moreover, due to the high temperatures present in the core jet [13], research has been undertaken in order to assess the limitations of RANS CFD for predicting heated nozzle flows [17,18].…”
Section: Computational Methods For the Calculation Of Exhaust System Flowsmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, there have been numerous investigations within the literature on the use of RANS CFD for the calculation of aerodynamic performance metrics for civil separate-jet nozzles [13,14,15,16]. Moreover, due to the high temperatures present in the core jet [13], research has been undertaken in order to assess the limitations of RANS CFD for predicting heated nozzle flows [17,18].…”
Section: Computational Methods For the Calculation Of Exhaust System Flowsmentioning
confidence: 99%
“…The gauge stream forces for the fan and core streams were evaluated from CFD computations through the integration of the momentum and pressure terms at the inlets of the respective duct, Eq. (14). Where is the fluid density, is the axial velocity and is the elemental surface area of the inlet boundary.…”
Section: The Experimental Nozzle Coefficients Reported By Mikkelsen Et Al Were Calculated Based On An Assumed Constantmentioning
confidence: 99%
“…The advent of Computational Fluid Dynamics (CFD) during the past two decades has rendered it a reliable and useful performance prediction tool for the aerodynamic analysis of exhaust nozzles [11,[15][16][17][18][19][20]. The associated flow phenomena observed in the vicinity of a gas-turbine engine exhaust system can be quite complex.…”
Section: Accepted Manuscript N O T C O P Y E D I T E Dmentioning
confidence: 99%
“…Many aircraft studies took place in 1973 when Boeing introduced computational fluid dynamic (CFD) as one of the aircraft research tools. Nowadays, many researchers have used CFD in aircraft studies to reduce the experimental cost as reported by Ismail and Wang [1], Sloan et al, [2] and Ives et al, [3] and Loutun et al, [4]. Ismail and Wang [1] employed CFD to study swirl flow of hot air for nacelle lip-skin application.…”
Section: Introductionmentioning
confidence: 99%